Histopathological evaluation of gastrointestinal stromal tumours - Bayramoğlu, Zeynep; Yılmaz Erözbek, Sıla; Kuzucular, Elif; Özden, Ferhat (Springer, 2022)
[Abstract Not Available]
Keywords: Histopathological; Gastrointestinal; Stromal Tumours